2012
DOI: 10.1002/rcm.5323
|View full text |Cite
|
Sign up to set email alerts
|

Studying ancient crop provenance: implications from δ13C and δ15N values of charred barley in a Middle Bronze Age silo at Ebla(NW Syria)

Abstract: The discovery of a storeroom full of barley and other cereals (L.9512) in the proto-historic site of Ebla has provided a unique opportunity to study the centralized storage system of the early city-state from a different perspective. Epigraphic evidence available within the site reveals a complex system of taxation which included gathering grain tributes from satellite sites and redistributing semi-finished products such as flour. In this paper, we intend to explore the possibilities of a combined approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 51 publications
0
21
1
Order By: Relevance
“…Nitrogen isotopic compositions were highly variable, particularly for potato, which most likely reflected variable local growing conditions (soil fertility, type of manure used) rather than any biochemical or physiological process specific to any particular plant species. Ultimately, the best source of baseline isotopic data for paleodietary studies may be from archaeobotanical remains [27], [201]–[203], provided that preservation of original carbon and nitrogen isotopic compositions can be demonstrated. Considerable work has been done in this regard for the isotopic composition of bone collagen [204][208] and to a lesser extent hair keratin [209], but a solid set of parameters for detecting preservation versus alteration of original plant carbon and nitrogen isotopic compositions have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen isotopic compositions were highly variable, particularly for potato, which most likely reflected variable local growing conditions (soil fertility, type of manure used) rather than any biochemical or physiological process specific to any particular plant species. Ultimately, the best source of baseline isotopic data for paleodietary studies may be from archaeobotanical remains [27], [201]–[203], provided that preservation of original carbon and nitrogen isotopic compositions can be demonstrated. Considerable work has been done in this regard for the isotopic composition of bone collagen [204][208] and to a lesser extent hair keratin [209], but a solid set of parameters for detecting preservation versus alteration of original plant carbon and nitrogen isotopic compositions have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the δ 15 N values of grains depend on soil conditions, such as the type of soil-N, the balance between enzyme demand and external concentration, and the manuring effect (cf. Fiorentino et al 2011;Aguilera et al 2008). The difference found in δ 15 N values between the Neolithic and historical bones in Mozuizi may be understood in the context of change through time of the soil content.…”
Section: Notementioning
confidence: 95%
“…In recent years, greater emphasis has been placed on direct means of inferring water conditions from archaeological crop remains themselves, through phytolith (Jenkins, Jamjoun and Al Nuimat 2011;Madella et al 2009;Mithen et al 2008;Piperno 2006;Rosen and Weiner 1994) and stable carbon isotope analysis (Araus and Buxó 1993;Araus et al, 'Changes' 1997a;Araus et al, 'Identification' 1997b;Araus, Febrero et al 1999;Araus, Ferrio et al 2007;Ferrio et al 2005;Fiorentino, Caracuta, Calcagnile et al 2008;Fiorentino, Caracuta, Casiello et al 2012;Flohr, Mülder and Jenkins 2011;Heaton et al 2009;Riehl 2008;Riehl, Bryson and Pustovoytov 2008;Stokes, Mülder and Jenkins 2011;Voltas, Ferrio et al 2008). Isotopic investigations have tended to interpret results in relative terms, for example using stable carbon isotopes to determine whether certain time periods were wetter or drier than others.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is only through the study of present-day crops, grown under known conditions, that the relationship between plant carbon isotopes, specific water conditions and water management practices can be explored. To date, such present-day studies have been conducted for only a handful of crop species, grown in few locations, under highly controlled experimental conditions (Araus et al, 'Identification' 1997b;Araus, Febrero et al 1999;Araus, Villegas et al 2003;Fiorentino, Caracuta, Casiello et al 2012;Flohr, Mülder and Jenkins 2011;Stokes, Mülder and Jenkins 2011).…”
Section: Introductionmentioning
confidence: 99%